REFORMS IN THE FIELD OF THE AUTOMOBILE TRANSPORT SYSTEM IN UZBEKISTAN DURING THE YEARS OF INDEPENDENCE AND THEIR RESULTS - Izatillo Omonov (Western European Studies, 2025)
The development of the transport infrastructure of the Republic of Uzbekistan, the emergence of a modern transport system, stabilization of the economy, the formation of a national transport system, the influence of highways on the economic development of the country
Keywords: Republic; transport; highwayshighways